2014
DOI: 10.1371/journal.pone.0092465
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Endocrine Disruption in Zebrafish Larvae after Exposure to Mono-(2-Ethylhexyl) Phthalate (MEHP)

Abstract: Phthalates are extensively used as plasticizers in a variety of daily-life products, resulting in widespread distribution in aquatic environments. However, limited information is available on the endocrine disrupting effects of phthalates in aquatic organisms. The aim of the present study was to examine whether exposure to mono-(2-ethylhexyl) phthalate (MEHP), the hydrolytic metabolite of di-(2-ethylhexyl) phthalate (DEHP) disrupts thyroid endocrine system in fish. In this study, zebrafish (Danio rerio) embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 52 publications
4
74
0
3
Order By: Relevance
“…These results, DEHP down-regulated the levels of THs and increased TRH expression in rats, are consistent with a previous study [20]. Another report that involved animal studies described that decreased the levels of serum T4 with prolonged DEHP exposure [21]. Similar results were found in epidemiological studies [18,19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results, DEHP down-regulated the levels of THs and increased TRH expression in rats, are consistent with a previous study [20]. Another report that involved animal studies described that decreased the levels of serum T4 with prolonged DEHP exposure [21]. Similar results were found in epidemiological studies [18,19].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have observed an inverse association between MEHP urinary concentrations and free T4 and T3 serum levels in men and similar negative correlations have been found in pregnant women [18,19]. In animal studies, rats and fishes fed with diets contaminated with DEHP were found to have thyroid alterations and lower plasma T4 concentrations [20,21]. But the detailed mechanisms that are involved in this process are unclear.…”
mentioning
confidence: 93%
“…Additionally, limited in vitro studies have shown that phthalates may have thyroid hormone receptor antagonist activity (Shen et al 2009; Sugiyama et al 2005). Several studies have also demonstrated potential phthalate actions on thyroid hormone biosynthesis and biotransport (Breous et al 2005; Ishihara et al 2003; Liu et al 2015; Wenzel et al 2005; Zhai et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Animal and in vitro studies suggest that phthalates may be capable of disrupting circulating thyroid hormone levels, although the exact biological mechanism(s) of action remain unclear (Boas et al 2012; Liu et al 2015; Zhai et al 2014). Additionally, a limited number of epidemiological studies have shown that phthalates may alter thyroid hormone levels in adult men and nonpregnant women as well as children (Boas et al 2010; Meeker et al 2007; Meeker and Ferguson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Flame retardants, polychlorinated biphenyls (PCBs), perfluorinated chemicals (PFCs), pesticides, phtalates, polycyclic aromatic hydrocarbons (PAHs), pharmaceutical residues and metals have been reported as thyroid disrupters in teleosts (Chan and Chan, 2012;He et al, 2012;LeRoy et al, 2006;Mukhi and Patiño, 2007;Park et al, 2011;Zhai et al, 2014). They alter the thyroid hormonal balance by affecting the different sites within the HPT axis, including iodine uptake, THs synthesis, activation, transportation and interaction with TRs, post-translational regulation, conjugation reactions and excretion (Fig.…”
Section: Environmental Pollutantsmentioning
confidence: 99%